Tiktok dan Shopee Live: Solusi Transformasi Pemasaran dan Peningkatan Daya Saing UMKM Kacang Intip - Marpaung, Durahman; Bakti, Surya (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2023)
In Batu Bara Regency, North Sumatra, Indonesia, significant economic transformation has occurred by developing Micro, Small, and Medium Enterprises (MSMEs) based on chili agriculture. Lubuk Cuik Village, one of the region's largest chili producers, has become the focus of economic empowerment through MSMEs. The community service program "Tiktok and Shopee Live: Solutions for Marketing Transformation and Competitiveness Enhancement of Kacang Intip MSMEs" was conducted by Muhammadiyah Kisaran College of Economics and involved interns and accompanying lecturers. This program aims to increase MSME sales, especially the Kacang Intip product, by utilizing digital marketing on platforms like TikTok and Shopee Live. Training and mentoring were combined with socialization on the importance of digital marketing management, collaboration with local influencers, and product visibility enhancement. The service results show an increase in the effectiveness of digital marketing, proving the importance of social media in expanding market reach and increasing sales. The study also identified challenges like limited time and the number of MSMEs involved. In conclusion, using digital media is critical to enhancing the competitiveness of MSMEs in Batu Bara Regency, especially in the chili industry.